(untitled) (Asian Journal of Pharmaceutics (AJP), 2015)
Proniosomes gel is semisolid liquid crystal products of nonionic surfactants, which converted into niosomes upon hydration. A proniosome based transdermal drug delivery system of granisetron hydrochloride (GRA HCL) developedÂ by coacervation phase separation method. Formulation optimized by use of 32 full factorial design. Span 60 and cholesterolÂ selected as independent variables, while entrapment efficiency (EE) and flux selected as dependent variables. ProniosomesÂ evaluated for EE, in vitro permeation study, stability study, microscopial examination by photomicroscopy, scanning electronÂ microscopy, particle size analysis. F5 batch containing 90 mg span 60, and 10 mg cholesterol show maximum entrapmentÂ (66.57 Â± 0.20%) and flux (7.94 Â± 0390 Î¼g/cm2/h). Comparative in vitro drug release study of plain drug solution andÂ drug in proniosomal gel form was carried out for 48 h on guinea pig skin. It was found that cumulative release and flux ofÂ proniosomal gel was nearly two times more than drug solution containing same drug concentration.The study demonstratedÂ the effectiveness of proniosomal transdermal patch containing GRA HCL for effective management of chemotherapy inducedÂ nausea and vomiting. Key words: Factorial design, industry feasible, niosomes, proniosomes, stability, transdermal drug delivery